Training Need of Farmers in Horticultural Crops in Haryana - Rani, Sonia; Kumar, Pawan; Saharawat, P S; Malik, Joginder Singh (Indian Journal of Extension Education, 2021)
Value addition in agriculture predominantly offers a means to increase, rejuvenate andÂ stabilize farm income. Value-added agriculture is fundamentally market-driven. It needs trained and skilled manpower to cope with the demand of rapidly changing markets. TheÂ present study was conducted in Haryana state and two districts Hisar from southwest and Sonipat from northeast were selected, purposively. From each district, three blocksÂ were selected randomly. Further, three villages were selected from each block making aÂ total of 18 villages. From each village, ten farmers were selected randomly, making a totalÂ sample of 180 farmers. It was found that majority of the respondents were interested in taking training of â€˜Farm level packaging and storageâ€™, â€˜Development of commercialÂ horticultural nursery for fruit trees and vegetables cropsâ€™, â€˜Processing and value additionâ€™ and â€˜Packaging of nursery plantsâ€™. DAE (Directorate of Agriculture Extension) should arrangeÂ training programmes based on the necessity of the farmers. Otherwise, it will not bringany positive outcome in the crop production systems of Haryana.